2011
DOI: 10.1093/ecam/nep157
|View full text |Cite
|
Sign up to set email alerts
|

Excoecarianin, Isolated from Phyllanthus urinaria Linnea, Inhibits Herpes Simplex Virus Type 2 Infection through Inactivation of Viral Particles

Abstract: Phyllanthus urinaria Linnea (Euphorbiaceae) is one of the traditional medicinal plants widely used by oriental people to treat various diseases. We have previously demonstrated that the acetone extract of P. urinaria inhibits herpes simplex virus type 2 (HSV-2) but not HSV-1 infection. In a continuing effort to clarify the antiviral mechanisms of P. urinaria, we isolated the pure compound excoecarianin from the whole plant of P. urinaria through acetone extraction, and investigated its anti-HSV-1 and HSV-2 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 59 publications
2
26
1
Order By: Relevance
“…We have previously identified several tannins of various plant sources that exhibit potent antiviral activities against HSV-1 and HSV-2. These include 1,3,4,6-tetra-O-galloyl-␤-D-glucose (77), casuarinin (10), ent-epiafzelechin-(4␣3R8)-epiafzelechin (17), excoecarianin (16), geraniin (77), hippomanin A (76), prodelphinidin B-2 3Ј-O-gallate (11), prodelphinidin B-2 3,3Ј-di-O-gallate (12), pterocarnin A (13), and putranjivain A (14). Studies from other laboratories have also reported a series of tannins and related compounds capable of inhibiting HSV infections (25,56,64,71,72).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously identified several tannins of various plant sources that exhibit potent antiviral activities against HSV-1 and HSV-2. These include 1,3,4,6-tetra-O-galloyl-␤-D-glucose (77), casuarinin (10), ent-epiafzelechin-(4␣3R8)-epiafzelechin (17), excoecarianin (16), geraniin (77), hippomanin A (76), prodelphinidin B-2 3Ј-O-gallate (11), prodelphinidin B-2 3,3Ј-di-O-gallate (12), pterocarnin A (13), and putranjivain A (14). Studies from other laboratories have also reported a series of tannins and related compounds capable of inhibiting HSV infections (25,56,64,71,72).…”
mentioning
confidence: 99%
“…The cytotoxic effects of CHLA, CHLI, PUG, and PUN on the different cell types used in the present study were measured by the calorimetric XTT (2,3-bis[2-methoxy-4-nitro-5-sulfophenyl]-5-phenylamino)-carbonyl]-2H-tetrazolium hydroxide) assay as described previously with some modifications (16). Briefly, cells were seeded in 96-well plates (10 4 cells per well) and incubated overnight to form a monolayer.…”
mentioning
confidence: 99%
“…Virucidal effects of excoecarianin, casuarinin, and geraniin have been established as well [28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The only drawback of these limited anti-HSV drugs is the development of viral resistance against these treatments and drug toxicity (19)(20)(21). Drug-resistant viral strains were increasingly isolated from patients, in particular immunocompromised individuals (20).…”
Section: Treatments Of Herpes Simplex Virusmentioning
confidence: 99%
“…This revealed that excoecarianin primarily inactivate HSV-2 virus particles to prevent viral infection. It was also able to act synergistically with acyclovir to exhibit antiviral effect against HSV-2 infection in Vero cells (21).…”
Section: Phyllanthus Urinariamentioning
confidence: 99%